Testing Native Language Interference - Šurnaitė, A. (Kalbotyra, 1977)
The interference of the Lithuanian language in teaching and learning the negative form of English adjectives, the indefinite and negative adverbs, the Present Perfect, the Present Continuous, the Past Perfect, the word order of affirmative and interrogative sentences have been discussed in the present article. These tests can be helpful when making text-books, teaching programs and other aids but cannot test the leamers’ competence in English.